2018
DOI: 10.1371/journal.pone.0193317
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with changing indications for adenotonsillectomy: A population-based longitudinal study

Abstract: ObjectiveAdenotonsillectomy (AT) is one of the most common surgical procedures performed in children and adults. We aim to assess the factors associated with changes in the incidence of and indications for AT using population-level data.Study designThis retrospective cohort study investigated patients who underwent AT between 1997 and 2010 by using data from the Taiwan National Health Insurance Research Database. We examined surgical rates and indications by the calendar year as well as age, sex, hospital leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…Tonsillectomy was found to be common among school-going children who were mostly in middle school (57.9%), whereas a study conducted in Australia, by Tran AH et al, showed a high prevalence of tonsillectomy among children 5–9 years of age [ 17 ]. Around 39.2% of patients with tonsillectomy have a family income of up to 9000 SAR, suggesting a lower middle class, which is also supported by research showing that twice as many children with age <16 years belong to the lower socioeconomic class [ 11 , 18 , 19 ]. However, household income showed a weak association with tonsillectomy in many other studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 77%
“…Tonsillectomy was found to be common among school-going children who were mostly in middle school (57.9%), whereas a study conducted in Australia, by Tran AH et al, showed a high prevalence of tonsillectomy among children 5–9 years of age [ 17 ]. Around 39.2% of patients with tonsillectomy have a family income of up to 9000 SAR, suggesting a lower middle class, which is also supported by research showing that twice as many children with age <16 years belong to the lower socioeconomic class [ 11 , 18 , 19 ]. However, household income showed a weak association with tonsillectomy in many other studies [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 77%
“…Second, the indications for tonsillectomy were not explicitly confirmed, and it is uncertain whether the procedure was performed due to tonsillitis. However, it is well-documented that tonsillectomy is predominantly conducted to address the infectious complication of tonsillitis, and previous studies have indicated that treatment for recurrent infections or chronic inflammation is the most common reason for tonsillectomy across all age groups [ 26 ]. Third, since information on different types of psoriasis, such as guttate, inverse, pustular, erythrodermic, or plaque, was unavailable in our dataset, types of psoriasis were not specifically categorized and were included into one group overall.…”
Section: Discussionmentioning
confidence: 99%
“…We noted the strongest benefit to pain control in the younger children rather than in older children, who are known to struggle with pain after adenotonsillectomy. Most of the children in our trial were admitted for recurrent tonsillitis, which is the most common indication for adenotonsillectomy in children younger than 18 years old [18].…”
Section: Discussionmentioning
confidence: 99%